Genetic structure, UV-vision, wing coloration and size coincide with colour polymorphism in Fabriciana adippe butterflies - Polic, Daniela (Wiley-Blackwell, 2025)
Colour polymorphisms have long served as model systems in evolutionary studies and continue to inform about processes involved in the origin and dynamics of biodiversity. Modern sequencing tools allow for evaluating whether phenotypic differences between morphs reflect genetic differentiation rather than developmental plasticity, and for investigating whether polymorphisms represent intermediate stages of diversification towards speciation. We investigated phenotypic and genetic differentiation between two colour morphs of the butterfly Fabriciana adippe using a combination of ddRAD-sequencing and comparisons of body size, colour patterns and optical properties of bright wing spots. The silvery-spotted adippe form had larger and darker wings and reflected UV light, while the yellow cleodoxa form displayed more green scales and reflected very little UV, showcasing that they constitute distinct and alternative integrated phenotypes. Genomic analyses revealed genetic structuring according to source population, and to colour morph, suggesting that the phenotypic differentiation reflects evolutionary modifications. We report 17 outlier loci associated with colour morph, including ultraviolet-sensitive visual pigment (UVRh1), which is associated with intraspecific communication and mate choice in butterflies. Together with the demonstration that the wings of the adippe (but essentially not the cleodoxa) morph reflect UV light, that UV reflectance is higher in females than males and that morphs differ in wing size, this suggests that these colour morphs might represent genetically integrated phenotypes, possibly adapted to different microhabitats. We propose that non-random mating might contribute to the differentiation and maintenance of the polymorphism.